Expectation of parental control and the maintenance of bottle-feeding in childhood - Adriana Dantas Costa; Elaine Pereira da Silva Tagliaferro; Eliana Dantas Costa; Glaucia Maria Bovi Ambrosano; Rosana de Fátima Possobon (Elsevier, 2021)
Objective: To investigate association between parental locus of control (belief of individuals about what or who has control of the events of their lives) and bottle feeding habits among children from 3 to 5 years of age. Methodology: Parental locus of control validated in Brazil, and semi-structured questionnaire to obtain sociodemographic, health, and oral habit behaviors was applied to mothers of 992 preschool children. Outcome variable "use of feeding bottle" was studied according to the time of its use (≤36 months and >36 months). Simple logistic regression models were adjusted and raw odds ratios were estimated for variables of distal blocks, which contemplated parental locus of control, socioeconomic characteristics of family, and maternal habits. In the intermediate block, the variables for conditions of the child's birth and place of health care attendance during the prenatal period and early childhood were included. In the proximal block, the time of breastfeeding and pacifier use were reported. Variables were analyzed from the distal to the proximal block, and the individual analyses that presented p ≤ 0.20 remained in each model; included in the subsequent block were the variables with p ≤ 0.10, because this was a study of prevention. Results: Longer time of feeding bottle use was associated with the internal parental locus of control, mothers older than 31 years of age, white race, premature children, who used pacifiers and are treated in the private health system. Conclusions: Children who maintained the habit of feeding bottle use for a longer time were those whose mother presented an internal locus of control.